2000
DOI: 10.1111/j.1530-0277.2000.tb02060.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Adenylyl Cyclase Activity as a Trait Marker of Alcohol Dependence

Abstract: Background: There is compelling evidence that genetic factors play a major role in the development of alcohol dependence. Platelet adenylyl cyclase (AC) activity has been proposed as a biochemical marker for differentiating alcohol-dependent and nondependent subjects, but the sensitivity and specificity of this marker have not been ascertained. The objective of this study was to determine the sensitivity and specificity of platelet AC activity in identifying alcohol-dependent subjects and to ascertain the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…for depression (Mooney et al, 1988(Mooney et al, , 1998Garcia-Sevilla et al, 1990;Pandey et al, 1990a,b;Menninger and Tabakoff, 1997;Menninger et al, 2000;Hoffman et al, 2002;Hines and Tabakoff, 2005). The most recent of these studies demonstrated markedly lower levels of basal, forskolin-, cesium fluoride-, and Gpp(NH)p-stimulated platelet adenylyl cyclase activity in subjects with a history of major depression compared with control subjects (Hines and Tabakoff, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…for depression (Mooney et al, 1988(Mooney et al, , 1998Garcia-Sevilla et al, 1990;Pandey et al, 1990a,b;Menninger and Tabakoff, 1997;Menninger et al, 2000;Hoffman et al, 2002;Hines and Tabakoff, 2005). The most recent of these studies demonstrated markedly lower levels of basal, forskolin-, cesium fluoride-, and Gpp(NH)p-stimulated platelet adenylyl cyclase activity in subjects with a history of major depression compared with control subjects (Hines and Tabakoff, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There were differences in several ion channel subunits, including sodium, potassium, and chloride channels, that could affect neuronal excitability. Adenylyl cyclase 2 (Adcy2) was 1.3-fold lower in iP; differences in adenylyl cyclases have been implicated in alcoholism (Menninger et al, 2000). Protein kinases and phosphatases are important in signal transduction and second messenger systems.…”
Section: Howard J Edenbergmentioning
confidence: 99%
“…Blood was drawn by venipuncture in Vacutainer tubes that contained ethylenediaminetetraacetic acid for preparation of plasma (Menninger et al, 2000). Plasma samples were stored at Ϫ70°C until forwarded in dry ice to the Helsinki coordination center (Finland) and further to the Helsinki assay center for determination of ethanol and methanol.…”
Section: Blood and Urine Samplesmentioning
confidence: 99%